Impact energy in heat-treated aluminium alloy 6061 and 7075 - Zainuddin, Hikmah; Ali, Mohd Basri (Asian Research Publishing Network (ARPN), 2024)
Instrumented Charpy impact is one of the promising methods to assess the impact energy; toughness and resilience of a material. The test consists of the Charpy machine and instrumentation equipment which is the strain gauge and the data acquisition system. Impact energy evaluations are important to understand the material behaviour subjected to sudden impact loading. Aluminium 7075 has good strength strength-to-weight ratio than aluminium 6061 and hence the AL 7075 is usually used in the aerospace industry, whilst the AL 6061 is commonly used in the automotive industry. The objective of the study is to observe and analyse the impact response of the Aluminium 6061 and 7075 at different heattreated conditions; O-anneal and T6 temper. In addition to the impact energy absorbed value, the impact strain signal is recorded too. Theoretical impact energy is calculated as well based on the information given by the Charpy machine software. Aluminium 7075 exhibits a lower value of impact energy absorbed and a smaller area under the curve compared to Aluminium 6061. The energy absorption capacity for each material grade and heat-treated condition are different from one another. O-anneal aluminium has a lesser energy absorbed value and a smaller area under the curve than the T6 temper aluminium. The outcome reveals that the heat treatment process alters the material microstructure and mechanical properties, whereas in this study the impact energy responses are influenced by these circumstances. Moreover, the chemical composition of the aluminium alloy distinguishes these two grades from one another, thus resulting in different impact responses.